A highly efficient three-phase single drop microextraction technique for sample preconcentration1. Issue 9 (7th May 2015) - Jahan, Sharmin; Xie, Haiyang; Zhong, Ran; Yan, Jian; Xiao, Hua; Fan, Liuyin; Cao, Chengxi
<x xml:space="preserve">Abstract</x> A highly efficient three-phase single drop microextraction method is presented by using an organic–aqueous compound droplet and a microdevice.